Prognostic indicators in pituitary adenoma surgery: a comprehensive analysis of surgical outcomes and complications - Riley, George; Scheyer, Nicolas; Klein, Marc; Merlot, Isabelle; Guerci, Bruno; Jeanbert, Elodie; Demarquet, Lea (Frontiers in Endocrinology, 2024)
Objective: The primary aim of this study was to identify predictive factors associated with onset of de-novo clinically significant pituitary insufficiencies following endoscopic endonasal surgery (EES) for pituitary adenomas. The secondary objective explored the predictive factors of surgical success.Methods: A retrospective analysis was conducted on 211 patients who underwent EES. Logistic regression models were employed for the primary and secondary objectives. Patients were stratified into specific groups based on surgical indications and prolactin levels for nuanced analysis.Results: Significant predictors for de-novo pituitary insufficiencies included male sex (OR 3.3, CI95% 1.3-8.1, p=0.01), immediate postoperative insufficiencies (OR 5.6, CI95% 2.8-11.1, p<0.001), and HYPRONOS criteria (OR 5.7, CI95% 1.6-20.9, p=0.008). For surgical success, preoperative insufficiencies (OR 0.7, CI95% 0.5-0.9, p=0.008), repeat surgeries (OR 0.1, CI95% 0-0.4, p=0.001), and gonadotroph or somatotroph adenomas were significant. Age and adenoma size were not predictive in multivariate analysis. Furthermore, we observed a "dip and recover" effect of prolactin after surgery and lower prolactin levels at follow-up (< 3 ng/ml) are correlated with more anterior pituitary insufficiencies than normoprolactinemic patients (p = 0.004).Conclusion: This study identifies key predictors for outcomes in pituitary surgery. Our research is the first to employ individualized success criteria for EES, challenging existing perceptions about the role of age and adenoma size. These findings open avenues for nuanced, individualized preoperative risk assessment and postoperative management.